IMPLEMENTATIONS OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE THERAPY FOR TREATING SLEEP DISORDERS IN CHRONIC KIDNEY DISEASE (CKD) PATIENTS AT MOHAMMAD HOESIN GENERAL HOSPITAL - Walensya Laura Agatha Hutabarat; Lisa Rizky Amalia (Spectra Clinical Case Reports Journal, 2025)
Sleep pattern disturbance is a common nursing problem in Chronic Kidney Disease (CKD) patients undergoing hemodialysis. Spiritual Emotional Freedom Technique (SEFT) is a non-pharmacological intervention that may improve sleep quality through physical stimulation and spiritual relaxation. This case study aimed to describe the implementation of nursing care in CKD patients with sleep disturbances and to evaluate the effectiveness of SEFT therapy. The study involved three inpatients with CKD undergoing hemodialysis. Assessment results showed similar complaints among patients, including difficulty initiating sleep, frequent awakenings, dissatisfaction with sleep, altered sleep patterns, and inadequate rest. Based on these findings, the nursing diagnoses established were sleep pattern disturbance, ineffective peripheral perfusion, fatigue, acute pain, nausea, and ineffective breathing pattern. Nursing care planning prioritized sleep support, circulation care, energy conservation, pain and nausea management, and respiratory monitoring. SEFT therapy was provided as a complementary intervention for 10–20 minutes daily over three consecutive days. After therapy, all three patients demonstrated improved sleep quality marked by reduced sleep onset latency, fewer nighttime awakenings, and increased feelings of restfulness. The mechanism of SEFT therapy involves tapping on body meridian points, which stimulates the parasympathetic nervous system, promotes relaxation, and enhances sleep-regulating hormones such as melatonin, serotonin, and oxytocin. These physiological effects help reduce stress responses and increase comfort levels. In this case study, the use of SEFT therapy was associated with observed improvements in sleep pattern disturbances among CKD patients; however, these findings are limited to the reported cases and cannot be generalized to other populations with similar conditions.